Growing up in ancient Israel: children in material culture and biblical texts - Garroway, Kristine Henriksen (Archaeology and Biblical Studies, 2018)
Cover -- Contents -- Preface -- List of Tables and Figures -- Abbreviations -- Introduction -- What to Expect When You're (Not) Expecting -- How to Birth a Baby -- The Newborn: Postpartum Rituals and Practices -- Inside Out: How to Ward off Evil from Belly through Birth -- Gendering, Engendering, and Educating the Growing Child -- Dressing Up -- Playtime -- Till Death Do Us Part -- Concluding Remarks -- Bibliography -- Ancient Sources Index -- Modern Authors Index